Pemanfaatan Media Sosial Untuk Pelayanan Kesehatan: Analisis Bibliometrik - Ahmad Palemba; Achmad Nurmandi (The Journal of Society and Media, 2023)
This study aims to analyze the role of social media in using public policy on health services in the literature Scopus indexed. Deep social media government has become more critical in e-government. Considering social media for taking the policy, the government is the internal medium to push public policy on services and health to increase the government's performance. This research analyzed 454 Scopus database documents from 2018-2023 using "health service," "policy," and "service use" as keywords. The data was filtered using bibliometrics based on the relevance of keywords, author's country, and year of publication, limited to the last five years. Information is saved in RIS format and processed through device soft Citespace. CiteSpace software is used for publication data visualization and government plan formulation. Effective social media policy requires good management for public decision-making. The study analyzed only one topic on Scopus without using international index databasesI'll summarize three research by presenting papers based on criteria like publications, origin countries, fields of study, authors, institutions, issues, and citations. Medicine studies with percentages are dominant, King's College London leads, Draheim contributes the most, and the US is the biggest contributor.